Rehabilitation of Partially Corrosion-Damaged Post-Tensioned Concrete Structures Using Carbon Fiber Reinforced Polymer - Alsuwaidi, Hadif; Habib, Ahed; Al-Sadoon, Zaid A.; Maalej, Mohamed; Altoubat, Salah; Barakat, Samer; Junaid, M. Talha (Civil Engineering Journal, 2025)
This study provides a comprehensive assessment of the deterioration and rehabilitation of post-tensioned (PT) concrete structures affected by chloride-induced corrosion. Through a detailed case study in the United Arab Emirates, the research identifies moisture ingress and inadequate waterproofing as primary contributors to corrosion in PT tendons and ducts, significantly compromising structural integrity. A rigorous evaluation using nondestructive and semi-destructive testing techniques was conducted to quantify damage and determine the extent of degradation. The results revealed severe corrosion in critical structural elements, necessitating targeted intervention to restore performance and durability. To address these challenges, an integrated rehabilitation strategy was developed, incorporating structural repairs, strengthening through carbon fiber-reinforced polymer (CFRP), and advanced waterproofing techniques. The adopted approach involved enlarging load-bearing components and applying CFRP to enhance flexural strength while minimizing aesthetic alterations. Experimental findings demonstrated that CFRP reinforcement increased slab flexural strength by 30% and reduced crack widths by 23%, effectively mitigating corrosion-related deterioration and extending service life. Furthermore, micro-concrete was utilized in all enlargement locations in compliance with ACI standards, ensuring long-term durability. The proposed rehabilitation framework offers a sustainable solution for extending the service life of PT structures exposed to aggressive environmental conditions. By addressing both immediate structural deficiencies and underlying degradation mechanisms, the strategy enhances resilience and reduces future maintenance requirements. The integration of CFRP strengthening, epoxy crack injection, and advanced waterproofing measures significantly improves corrosion resistance and structural longevity.